PENGARUH SEBELUM DAN SESUDAH MELAKUKAN MOBILISASI DINI TERHADAP PERUBAHAN TINGKAT NYERI PADA KLIEN POST OPERASI APENDIKS DI RUMAH SAKIT ROYAL PRIMA TAHUN 2021 - Vera harahap, Angelica SIahaan (Tanjungpura Journal of Nursing Practice and Education, 2021)
Background: Appendectomy is surgery to remove the appendix. Appendectomy should be performed immediately to reduce the risk of perforation. Appendectomy can be performed under general anesthesia with lower abdominal surgery. Early mobilization is a movement of the muscles of the body that is carried out as early as possible, the first 24 hours after surgery, the purpose of early mobilization is to increase circulation and prevent contractures and also allow the client ito return to full physiological function.Purpose: This study was to analyze the effect of giving early mobilization to changes in pain in post-appendiceal surgery clients in appendectomy patients in the Royal Prima Hospital inpatient room in 2021.Methods: This research is a One Group Pretest-Posttest Design study nvolving 38 respondents.Results: research obtained through the Wilcoxon Test showed a p value of 0.000 0.05 so it was concluded that Ho was rejected and Ha accepted.Conclusion: the level of pain experienced by patients after early mobilization of post appendix surgery clients at RSU Royal Prima is slightly more painful and the minority feels more pain.Keywords: Appendix, Early Mobilization, Pain